Efforts to Form True Muslim Character Based on Family Education - Sri Widaningsih; Fia Alifah Putri (Yayasan Zia Salsabila, 2023)
Morality is an important concern in the world of education, considering that the progress of all-sophisticated technology is not followed by an improvement in the attitude (behavior) of educational alumni. Thus, synergy is needed between educational institutions, both formal, informal and non-formal, especially the family environment. This research aims to analyze efforts to form true Muslim character based on family education. This type of research uses a qualitative approach with a literature study method. Data sources are quoted from credible pages such as Google Scholar and SINTA. Next, the data was analyzed and checked for validity through data triangulation. The results of this research conclude that (1) the role of parents in forming children's character includes; praying for goodness for children, teaching and giving examples of goodness for children, and appreciating every child's good behavior; and (2) parents provide guidance and spectacle that can help children's moral and religious development, as well as monitor children's behavior.